The MITC4+ shell element and its performance. (June 2016) - Ko, Yeongbin; Lee, Phill-Seung; Bathe, Klaus-Jürgen
Highlights: An effective new 4-node shell element is derived from the MITC4 shell element. A new assumed membrane strain field is developed to alleviate membrane locking. The numerical results show the improved predictive capability. Abstract: The objective in this paper is to improve the performance of the 4-node MITC quadrilateral shell finite element, referred to as the MITC4 element (Dvorkin and Bathe, 1984). We propose a new MITC4 shell element, the MITC4+ element, in which the mid-surface membrane strain components are assumed using the concept of the MITC method. The tying membrane strains are obtained from four triangular domains which subdivide the mid-surface of the 4-node quadrilateral shell element. This approach alleviates locking that can happen when the MITC4 shell elements are geometrically distorted in curved geometries. Several basic tests including the isotropy, zero energy mode, and patch tests are performed. Through the solution of various shell problems, the convergence behavior of the MITC4+ shell element is studied to show the improvements reached.